Model-based Product Configuration in Augmented Reality Applications - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Augmented Reality (AR) has recently found high attention in mobile shopping apps such as in domains like furniture or decoration. Here, the developers of the apps focus on the positioning of atomic 3D objects in the physical environment. With this focus, they neglect the conﬁguration of multi-faceted 3D object composition according to the user needs and environmental constraints. To tackle these challenges, we present a model-based approach to support AR-assisted product con-ﬁguration based on the concept of Dynamic Software Product Lines. Our approach splits products (e.g. table) into parts (e.g. tabletop, ta-ble legs, funnier) with their 3D objects and additional information (e.g. name, price). The possible products, which can be conﬁgured out of these parts, are stored in a feature model. At runtime, this feature model can be used to conﬁgure 3D object compositions out of the product parts and adapt to user needs and environmental constraints. The beneﬁts of this approach are demonstrated by a case study of conﬁguring modular kitchens with the help of a prototypical mobile-based implementation.
Keywords: Product Configuration; Augmented Reality; Runtime Adaptation; Dynamic Software Product Lines

Run2Survive: A Decision-theoretic Approach to Algorithm Selection based on Survival Analysis - Tornede, Alexander; Wever, Marcel Dominik; Werner, Stefan; Mohr, Felix; Hüllermeier, Eyke (ACML 2020)
Algorithm selection (AS) deals with the automatic selection of an algorithm from a fixed set of candidate algorithms most suitable for a specific instance of an algorithmic problem class, where "suitability" often refers to an algorithm's runtime. Due to possibly extremely long runtimes of candidate algorithms, training data for algorithm selection models is usually generated under time constraints in the sense that not all algorithms are run to completion on all instances. Thus, training data usually comprises censored information, as the true runtime of algorithms timed out remains unknown. However, many standard AS approaches are not able to handle such information in a proper way. On the other side, survival analysis (SA) naturally supports censored data and offers appropriate ways to use such data for learning distributional models of algorithm runtime, as we demonstrate in this work. We leverage such models as a basis of a sophisticated decision-theoretic approach to algorithm selection, which we dub Run2Survive. Moreover, taking advantage of a framework of this kind, we advocate a risk-averse approach to algorithm selection, in which the avoidance of a timeout is given high priority. In an extensive experimental study with the standard benchmark ASlib, our approach is shown to be highly competitive and in many cases even superior to state-of-the-art AS approaches.

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbrügger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP)

Local Graph Transformation Primitives For Some Basic Problems In Overlay Networks - Setzer, Alexander

When Donors Turn into Acceptors: Ground and Excited State Properties of FeII Complexes with Amine-Substituted Tridentate Bis-imidazole-2-ylidene Pyridine Ligands - Vukadinovic, Yannik; Burkhardt, Lukas; Päpcke, Ayla; Miletic, Anabel; Fritsch, Lorena; Altenburger, Björn; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)

A Group Signature Scheme from Flexible Public Key Signatures and Structure-Preserving Signatures on Equivalence Classes - Schürmann, Patrick

Enhancing Security by Usage of Universal One-Way Hash Functions - Terfort, Tobias

Algorithmen für selbststabilisierende Skip+-Delaunaygraphen - Guggenmos, Andreas

Strukturoptimierung einer Messradkomponente zur realitätsnäheren Erfassung von Fahrzeuglastdaten und Bruchmechanische Bewertung - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Joy, T.D.; Neumann, J.; Vidner , J.; Kullmer, G.; Richard, H.A. (DVM-Bericht 252, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Einsatz von Topologieoptimierungssoftware - Der Ersatz für den Ingenieur? - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Kullmer, G.; Richard, H.A. (DVM-Bericht 405, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Implementierung additiver Fertigungsverfahren in den chirurgischen Arbeitsablauf - Risse, L.; Kullmer, G. (DVM-Bericht 405, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Digitale mehrseitige Plattformen – Besser verstehen, wie digitale Plattformen funktionieren - Kundisch, Dennis

Influence of Part Microstructure on Mechanicl Properties of PA6X Laser Sintered Specimens - Kummert, Christina; Diekmann, Wolfgang; Tews, Katrin; Schmid, Hans-Joachim (29th Annual International Solid Freeform Fabrication Symposium)

Das Technologiedesign umfassend und strukturiert anpassen - Kundisch, Dennis

Förderung von Kompetenzen im Bereich Wirtschat 4.0 an Fachschulen - Kundisch, Dennis

A new hydrodynamic analogy model for the determination of transport phenomena in random packings - Salten, Alexander Heinrich Johannes; Maćkowiak, Jan F.; Maćkowiak, Jerzy K.; Kenig, Eugeny (Chemical Engineering Science)

Einfluss der Füllkörpergeometrie und Strömungsformen auf die Trennleistung von Absorptionskolonnen - Salten, Alexander Heinrich Johannes; Ehlert, Thomas; Maćkowiak, J. F.; Maćkowiak, J.; Kenig, Eugeny
Keywords: PubList

Entwicklung eines Gitterfüllkörpers ENVIPAC 4 unterstützt durch prädiktive Modellierung - Maćkowiak, J. F.; Maćkowiak, J.; Salten, Alexander Heinrich Johannes; Kenig, Eugeny
Keywords: PubList

Entwicklung modellbasierter Werkzeuge zur Vermeidung von Notfallsituationen bei der chemischen Absorption - Bothe, Mike; Fedorov, Alexander; Frei, Herrmann; Lutters, Nicole; Kenig, Eugeny

Numerische Simulation von Gravidestillationsapparaten zur Trennung eines binären Ethanol/Wasser‐Gemisches - Wende, Marc; Philippi, K.; Kenig, Eugeny (Chemie Ingenieur Technik)